Air pollution, prevention and control methods - the need for change seen by young people - Soler Segovia, David; Kostecka, Joanna (Uniwersytet Rzeszowski: Południowo-Wschodni Oddział Polskiego Towarzystwa Inżynierii Ekologicznej z siedzibą w Rzeszowie, 2018)
Air pollution is a major problem nowadays, due to its importance as a source of other environmental problems, such as global warming and climate change, as well as their impact on worldwide health. Different studies support that this situation can be turned around, by applying diverse actions at different scales; individual, industrial and governmental. The exemplary programmes presented in this paper can be easily adapted by the interested and with their help education for sustainable development (including activities for clean air), can be implemented, similarly to the Faculty of Biology and Agriculture at the University of Rzeszów.

Zanieczyszczenie powietrza jest obecnie poważnym problemem, ze względu na jego znaczenie jako źródła innych problemów środowiskowych, takich jak globalne ocieplenie i zmiany klimatu, a także ich wpływ na zdrowie na całym świecie. Badania potwierdzają, że można odwrócić tę sytuację, stosując działania w różnych skalach; indywidualnej, przemysłowej i rządowej. Przykładowe programy przedstawione w opracowaniu mogą być łatwo zaadaptowane przez zainteresowanych, a przy ich pomocy można wdrożyć edukację na rzecz zrównoważonego rozwoju (z uwzględnieniem działań na rzecz czystego powietrza), podobnie jak na Wydziale Biologiczno-Rolniczym Uniwersytetu Rzeszowskiego.
Keywords: air pollution; sustainable development; prevention; control; educational programmes; zanieczyszczenie powietrza; zrównoważony rozwój; zapobieganie; kontrola; programy edukacyjne